IMPROVING THE ORGANIZATION OF EVENTS IN BUSINESS HOTELS: ANALYTICS AND PRACTICAL SOLUTIONS - Милка, Діана; Пушка, Ольга; Дулька, Ольга; Шидловська, Олена; Іщенко, Тетяна (SWorldJournal, 2025)
The article examines the role of event services as a key strategic component in the development of the hotel business under modern market conditions. It provides an in-depth analysis based on the case of Kyiv hotels, which retain their status as Ukraine’s